Encapsulation of MPEG-4 streams over ATM adaptation layers - Zeng, Xing (2008)
The MPEG-4 multimedia standard opens opportunities to deliver multimedia content over numerous network technologies. This project aims to derive an encapsulation scheme for carrying MPEG-4 streams over ATM adaptation layers. To achieve this purpose, the classification of MPEG-4 streams and their characteristics are studied, the object descriptor framework is looked into to gain an insight of the relationships between MPEG-4 streams. The four adaptation layers (AAL) of the ATM network are compared to find out the most suitable AAL for the encapsulation purpose. Some proposals dealing with transportation of MPEG-4 streams are surveyed to obtain an understanding of issues facing the encapsulation of MPEG-4 streams.